Relationship between damage and hardness profiles in ion irradiated SS316 using nanoindentation – Experiments and modelling. (November 2016) - Saleh, Michael; Zaidi, Zain; Ionescu, Mihail; Hurt, Christopher; Short, Ken; Daniels, John; Munroe, Paul; Edwards, Lyndon; Bhattacharyya, Dhriti
Abstract: In this work, the authors apply the "top-down" nanoindentation testing method to assess the mechanical property changes in ion-irradiated metallic alloys for three different ion energies in order to understand the relationship between ion energy, damage peak depth and hardness peak depth. The samples were irradiated with He +2 ions having 1, 2 and 3 MeV beam energies respectively. The curves for ΔH (radiation induced hardness) have been obtained by calculating the difference of the irradiated and unirradiated hardness curves after these were corrected for indentation size effect. Three-dimensional analytical and numerical models have been developed to obtain greater insight into the mechanisms involved in the nanoindentation processes, the nature of the plastic zone, and how these affect the hardness results, including the full hardness profiles with respect to depth. This is particularly valuable in situations where the damage profile is non-uniform, as in the present case, and provides the means to predict expected hardness peak positions and values for a given irradiation dose. Graphical abstract: Highlights: Nanoindentation of SS316 irradiated by 1–3 MeV He 2+ ions for hardness-depth curves. Hardness profiles corrected for indent size effect, ΔH(Rad-Virgin) curves evaluated. Linear correlation between damage and hardness profiles (as function of energy). 3D finite element model developed; double dished plastic volume; H curve predicted. 3D analytical model developed, hardness curves calculated for all energies.